CHARITY IN THE FOUNDATION AND DEVELOPMENT OF SUNDAY SCHOOLS IN UKRAINE 1860-1862 - NARADKO, Andriy; PEREDERII, Iryna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
The article considers the issue of charitable assistance in the process of creation and development of Sunday schools. The reasons for the emergence of a new type of educational institution for the Russian Empire are determined. Raising public awareness, the process of Ukrainian national and cultural revival, accelerating economic development and the urgent need of children and adults for education lead to the formation of new educational institutions. The source base of the study shows the high interest of researchers in the emergence and development of Sunday schools in Ukraine. Most of these works are devoted to the historical and pedagogical component of the activities of these educational institutions. Charitable activities played an important role in the creation of a network of primary education institutions in Ukraine. The system of Sunday schools was formed exclusively on1 charitable activities. These schools did not have permanent sources of funding. In addition to general Sunday schools for adults and working children, denominational schools were created for students of different religions. All segments of society took part in the founding of Sunday schools. Sunday schools, uncontrolled by the authorities, were seen as dangerous hotbeds of free thought. A powerful public initiative did not stop the establishment and further activity of Sunday schools until the early twentieth century. The total amount of charitable assistance to Sunday schools is difficult to calculate. A significant part of it was provided in non-monetary form.